2004
DOI: 10.1002/aqc.602
|View full text |Cite
|
Sign up to set email alerts
|

Dusky dolphin foraging habitat: overlap with aquaculture in New Zealand

Abstract: ABSTRACT1. Marine farms have the potential to affect dolphin foraging in the coastal environment, yet this issue has been largely omitted from aquaculture management models. Data on the subject are minimal. This study was conducted to examine potential overlap between dusky dolphin habitat use and New Zealand's growing green-lipped mussel farming industry.2. Data on dusky dolphin occurrence, distribution, abundance, and behaviour were collected from small vessels over five successive winters in the Marlborough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 30 publications
4
77
0
Order By: Relevance
“…This region has been characterized by high primary productivity due to unique local oceanographic conditions (Heath 1985). These conditions underlie the presence of a large number of marine mammals and seabirds (Markowitz et al 2004, Vaughn et al 2008. The study was conducted under Texas A&M Animal Use Protocol 2005-48.…”
Section: Methodsmentioning
confidence: 99%
“…This region has been characterized by high primary productivity due to unique local oceanographic conditions (Heath 1985). These conditions underlie the presence of a large number of marine mammals and seabirds (Markowitz et al 2004, Vaughn et al 2008. The study was conducted under Texas A&M Animal Use Protocol 2005-48.…”
Section: Methodsmentioning
confidence: 99%
“…The dusky dolphin Lagenorhynchus obscurus is a similarly sized species that resides in the cold-temperate waters around New Zealand, western South Africa, and South America (Gaskin 1968, Van Waerebeek et al 1995. Dusky dolphins in shallow bays feed during the day on small schooling fish (Wür-sig & Würsig 1980, Markowitz et al 2004, while in the waters of Kaikoura Canyon, New Zealand dusky dolphins feed at night on mesopelagic micronekton in a sound-scattering layer (Cipriano 1992, Würsig et al 1997. Off both Hawaii and Kaikoura, the behavior of the mesopelagic animals combined with the local topography brings these prey layers unusually close to the shoreline (Robertson et al 1978, Cipriano 1992, Benoit-Bird et al 2004, Benoit-Bird & Au 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Markowitz et al (2004) described effects of mussel farms on dusky dolphins. They found that Admiralty Bay was an important winter foraging habitat for dusky dolphins and that dusky dolphins rarely used habitat within mussel farms.…”
Section: Introductionmentioning
confidence: 99%